Determining the Patient Acceptable Symptomatic State for the ASES, SST, and VAS Pain After Total Shoulder Arthroplasty - Aaron M Chamberlain MD, MSc; Man Hung PhD; Wei Chen PhD; Jay D Keener MD; Jared McAllister MD; Gregory Ebersole MS; Erin K Granger MPH; Randy C Bowen MS; Robert Z Tashjian MD (Journal of Shoulder and Elbow Arthroplasty, 2017)
Background The Patient Acceptable Symptom State (PASS) is a symptom state that a patient considers acceptable. No prior study has determined the PASS for the American Shoulder and Elbow Surgeons (ASES) score, the Simple Shoulder Test (SST), and the Visual Analog Scale (VAS) pain score after shoulder arthroplasty. The purpose of this study was to determine the PASS for the ASES score, the SST score, and VAS pain for patients treated with a total shoulder arthroplasty. Methods A total of 326 patients had a primary anatomic total shoulder arthroplasty (TSA) or primary reverse total shoulder arthroplasty (RSA) by 1 of 5 shoulder and elbow surgeons at 1 of 2 institutions. Each patient completed the SST, ASES score, and a VAS pain preoperatively and at a minimum of 2 years postoperative (average 3.5 years). The PASS value for the ASES score, SST, and VAS pain was calculated. Results The PASS for the ASES score, SST, and VAS pain was 76, 8.4, and 1.5, respectively. Neither hand dominance nor age had a significant effect on PASS for SST, VAS, and ASES ( P  > .05). Gender had significant effect on SST and ASES scores with P -values of < .01 and .034, respectively. Duration of follow-up is correlated with VAS ( P  = .004) but not with ASES or SST scores. Conclusions Patients treated with a shoulder arthroplasty consider ASES score of 76, SST score of 8.4, and a VAS pain level of 1.5 to be acceptable symptomatic states. Females typically consider a slightly higher ASES and SST score to reach an acceptable state.